PERAN INFLUENCER DALAM MEMBENTUK KESEJAHTERAAN KONSUMEN UNTUK MENINGKATKAN NIAT BELI - WIJANARKO, FAIQ RAIHAN; Masnita Siagian, Yolanda (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze the role of influencers in shaping consumer well-being to increase purchase intention. The instrument used to measure the research variables has passed the validity and reliability tests. Sampling was carried out using the non-probability sampling method with a purposive sampling technique. The respondent criteria in this study were men who were followers of social media influencers of men's skincare products in the past month. A total of 206 respondents who met the criteria had filled out the questionnaire online via Google Form. The data obtained were processed using the Structural Equation Modeling (SEM) analysis method using AMOS software. The results of this study indicate that trustworthiness has a positive effect on stickiness in influencer posts, then stickiness in influencer posts has a positive effect on hedonic well-being and eudaimonic well-being, and ultimately consumer eudaimonic well-being has a positive effect on purchase intention. Therefore, managers can utilize the role of trusted influencers to increase consumer attachment and eudaimonic well-being which can ultimately increase purchase intention. However, this study found that physical attractiveness and expertise did not have a positive effect on stickiness in influencer posts. Consumer hedonic well-being also does not have a positive effect on purchase intention. Based on these findings, it is suggested that future research add gender and influencer reputation variables as moderating variables and add attitude variables toward influencers as mediating variables in the conceptual framework so that the research model becomes more comprehensive.